2020
DOI: 10.1249/mss.0000000000002455
|View full text |Cite
|
Sign up to set email alerts
|

Multifactorial Determinants of Running Injury Locations in 550 Injured Recreational Runners

Abstract: Purpose Despite the health benefits of running, the prevalence of running-related injuries (RRI) remains high. The underlying risk factors between these injuries are still not well understood. Therefore, the aim of this study was to compare biomechanical, anthropometric, and demographic injury risk factors between different locations in injured recreational runners. Methods In this retrospective case–control analysis, 550 injured runners (49.6% female) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 33 publications
1
33
0
1
Order By: Relevance
“…While the amount of loading is the key factor in the etiology of Achilles tendinopathy, there are several intrinsic (age, stress, genes, biomechanics, body composition) and extrinsic factors (footwear) modulating the risk for this injury [ 83 ]. Recent studies found biomechanical (footstrike pattern, ankle dorsiflexion moments) and training-related parameters (changes in training, cold weather, footwear, use of compression socks, mileage) as possible risk factors [ 10 , 51 , 84 86 ]. This summary of (possible) risk factors does not directly explain the increased probability for male runners to have an Achilles tendinopathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the amount of loading is the key factor in the etiology of Achilles tendinopathy, there are several intrinsic (age, stress, genes, biomechanics, body composition) and extrinsic factors (footwear) modulating the risk for this injury [ 83 ]. Recent studies found biomechanical (footstrike pattern, ankle dorsiflexion moments) and training-related parameters (changes in training, cold weather, footwear, use of compression socks, mileage) as possible risk factors [ 10 , 51 , 84 86 ]. This summary of (possible) risk factors does not directly explain the increased probability for male runners to have an Achilles tendinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…For injury prevention, risk factors need to be well understood [6]. Risk factors for running are manifold and consist of training load, biomechanical, anatomical and anthropometrical variables [7][8][9][10][11][12]. While some previous studies exclusively investigated either male [9,13] or female [14][15][16] runners, sex has been suggested to be a risk factor for specific injury patterns in running, as well as for overall injury risk [7,17,18].…”
Section: Introductionmentioning
confidence: 99%
“… 1 Some studies 57 , 66 have also combined MFS and FFS patterns, grouping them together as non-RFS. Studies that have reported FSP classifications have used visual analysis of sagittal plane video recordings, 11 , 21 , 32 , 61 , 66 categorization of continuous measures (foot and ankle contact angles and strike index [SI]), 14 , 15 , 18 , 45 , 48 , 53 or self-reporting methods. 25…”
mentioning
confidence: 99%
“…Moreover, the results from several studies note that the biomechanical benefit of specific footstrike patterns are conflicting (Stearne et al, 2014;Dudley et al, 2017), which has been supported by recent prospective injury studies in adults (Warr et al, 2015;Kuhman et al, 2016;Messier et al, 2018;Anderson et al, 2019). Other evidence from studies on adult runners suggest that footstrike more likely affects the risk of specific injuries, rather than one footstrike pattern being more or less injurious than another (Hollander et al, 2021a). Further research encompassing the effect of footstrike pattern on adolescent running gait relating to injury is warranted.…”
Section: Footstrike Mechanics and Kinematicsmentioning
confidence: 96%
“…Notably, early sport specialization in adolescent athletes is associated with increased sport-related injury risk, attributed in part to the homogeneity of movement patterns repetitively stressing the same immature tissues (Hamill et al, 2012;Post et al, 2017). Although associations between running biomechanics and overuse injuries have been widely studied in adults (Ceyssens et al, 2019;Hollander et al, 2021a), comparatively little research has targeted potential relationships between musculoskeletal injury and growth-related changes in biological age, body anthropometry, neuromuscular control, and running biomechanics in youth (Krabak et al, 2020). The aim of this perspective article was to provide a brief summary of the current epidemiology and etiology of RRI.…”
Section: Introductionmentioning
confidence: 99%